Sheikh Abul Hassan Ali Hassani Nadwi and His Contributions to The Sciences of Prophetic Hadith: A Concise Expository Study - Syed Abdul Majid Ghouri (FPPI, KUIS, 2024)
Sheikh Abul Hassan Ali Hasani Nadwi (d. 1999) was a world renowned Islamic scholar, outstanding preacher, a stalwart in Islamic thought, and known for his vivid writing. He combined between knowledge and character-speaking, besides having enlightened guiding thought and balanced preaching to the godly path. Muslims around the world benefited from his writings and works on preaching, Islamic thoughts and literature. He has contributed to the science of the Prophet’s Hadith through teaching and scientific writing of books on Hadith, its sciences and narrators. He was known for the strength of his isnad (the line of narrators of Hadith from the source), and many a Muslim scholar looked upon the ijaza (certification to transmit a particular source of Hadith) from him. However, this critical aspect of his outstanding scientific personality did not receive its due share of research. This oversight constitutes the driving motivation for this paper by following the scientific methodology of the study using a descriptive and inductive method. The paper comprises of four topics. First is a brief biography of Sheikh Nadawi and his scholarly attainments. Second is his dedication to the study and teaching of the Prophet’s Hadith. Third relates to his ijazā in Hadith. And, finally, the fourth part is an exposition on his written contribution in Hadith and its sciences. The paper concludes with a summary of some of the important findings: Sheikh Nadwi was a famous scholar among Muslims in this century, he received ijaza from great scholars of Hadith in his times, great scholars sought ijaza from him, and he served the cause of the science of Hadith through teaching, authorship and penning forwards for Hadith resources.